Aqueous processing of coconuts (Texas A & M) - Bantayan, Ronaldo C. (College of Engineering, 1977)
Capacity: coconuts 120 MT/day, insoluble protein 862 kg/day, coconut oil 11458 kg/day, skim milk concentrate 5274 kg/day, dried residue 3526 kg/day -- Plant location: San Pablo, Laguna -- Plant area: 50 m x 28 m -- Total capital investment: P 10,797,790 -- Annual cost of production: P 21,093,261 -- Annual sales: P 28,038,838 -- Annual income (before taxes): P 6,945,577 -- Rate of return on investment: 64% -- Payout time: 1.6 years -- Break-even point: 30%